Advances in building energy management systems (BEMS): A comprehensive review with bibliometric analysis and future research directions - Sihombing, Very; Yandri, Erkata; Pramono, Kukuh Priyo; Ariati, Ratna (National Research and Innovation Agency, 2025)
Building energy management systems (BEMS) are essential for enhancing energy efficiency and sustainability in buildings. This literature review analyzes BEMS research trends from 1982 to 2024, utilizing bibliometric analysis based on a dataset from Scopus. The study identifies key developments that influence all publications and emerging research topics in the field. While BEMS offers significant potential for real-time energy monitoring and control, challenges remain, including the need for standard protocols, improved cybersecurity, and cost-effective solutions for small buildings. This research highlights the importance of addressing these challenges to foster wider adoption of BEMS technology and contribute to a sustainable energy future. The findings aim to guide future research directions and enhance the implementation of BEMS in various building types.